Albumi gorskih fotografij (1920)
During World War I, the Slovenian Mountaineering Society lost a great part of its infrastructure. Fifteen mountain cabins were destroyed or abandoned while thirteen out of twenty-seven subsidiaries of the Society found themselves outside the borders of the new home country due to the Treaty of Rapallo and the Carinthian plebiscite. But as the newly founded Kingdom of Yugoslavia forbade all foreign societies, the Slovenian Mountaineering Society managed to take over some of the German mountain cabins which were then renamed. The first Slovenian mountaineering guide called Na planine! was written by Pavel Kunaver in 1921. The Interwar period was also the time of enhanced interest in alpinism that led to the foundation of the Skala Alpinist Club, and eventually, due to this club’s promotion of amateur photography, to the foundation of an amateur photographic section of the Club.In the digital collection before you we present mountain photography albums preserved by the National and University Library. The photographs were taken by different Slovenian photographers between the years 1920 and 1940.
In the digital collection before you we present  mountain photography albums preserved by the National and University Library. The photographs were taken by different Slovenian photographers between the years 1920 and 1940, and depict views one comes across in the mountain region of Slovenia.